Determinants of Nutritional Status of Primary School Children in Sangir Batang Hari District, Solok Selatan, West Sumatra, 2012 - Melvia, L; Denas, S; Deni, E (KnE Life Sciences, 2019)
Stunting is described as the nutritional status of primary school children with a shortage of energy and protein. Identifying factors associated with nutritional status is essential to avoid or reduce determinant factors and assumed to facilitate better advocacy in this district. This study aimed to assess the determinants of nutritional status of primary school children in Sangir Batang Hari District, Solok Selatan, West Sumatra, 2012. This research used a Cross-sectional community-based study that was conducted from January to July 2012 at three randomly selected primary school in Sangir Batang Hari district, Solok Selatan, West Sumatra. Quantitative data was gathered from 114 primary school children and their mothers. Chi-Square analysis was made to obtain p-value and confidence interval of statistical associations. 55.3% of respondents with high knowledge, 20.2% of respondents with food resistant household, 32.5% of the respondent with good energy intake, 90,4% of respondents with good protein intake, and 52.6% of respondents with normal nutritional status (Height/ Age). There was a significant relationship between energy and protein intake with nutritional status of primary school children, and there was no significant relationship between levels of mother knowledge and food security with nutrient intake of primary school children. The public health department and agriculture department must increase their cooperation in teaching their society to use the yard of the house to farming, and school health unit in primary school must always give health education to the students. Keywords: nutritional status; primary school children